2020
DOI: 10.1111/mec.15340
|View full text |Cite
|
Sign up to set email alerts
|

Insects and incest: Sib‐mating tolerance in natural populations of a parasitoid wasp

Abstract: Sib‐mating avoidance is a pervasive behaviour that is expected to evolve in species subject to inbreeding depression. Although laboratory studies provide elegant demonstrations, small‐scaled bioassays minimize the costs of mate finding and choice, and thus may produce spurious findings. We therefore combined laboratory experiments with field observations to examine the existence of inbreeding avoidance using the parasitoid wasp Venturia canescens. In the laboratory, our approach consisted of mate‐choice experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…Our results agree with suggestions made by previous studies that being dispersive is a good strategy to maintain genetic diversity at the CSD locus and alleviate extinction risk (Antolin & Strand, 1992; Collet et al., 2020; Cook & Crozier, 1995; Faria et al., 2016; Ruf et al., 2011; van Wilgenburg et al., 2006). Solitary parasitoids are generally good fliers (Godfray, 1994; van Wilgenburg et al., 2006).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results agree with suggestions made by previous studies that being dispersive is a good strategy to maintain genetic diversity at the CSD locus and alleviate extinction risk (Antolin & Strand, 1992; Collet et al., 2020; Cook & Crozier, 1995; Faria et al., 2016; Ruf et al., 2011; van Wilgenburg et al., 2006). Solitary parasitoids are generally good fliers (Godfray, 1994; van Wilgenburg et al., 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Inbreeding avoidance is one of the factors that can promote the evolution of dispersal (Saastamoinen et al., 2018). Field studies have shown that parasitoids can disperse for 10s of meters up to 7.5 km (Collet et al., 2020; Couchoux et al., 2016; Nair et al., 2016; Roland et al., 2000) and can be wind‐borne over several kilometers (Kristensen, Schellhorn, Hulthen, Howie, & De Barro, 2013). Wing polymorphism and sex‐biased dispersal have been documented in multiple species of parasitoids (Asplen et al., 2009; Collet et al., 2020; Godfray, 1994; Ruf et al., 2011), suggesting that dispersal is adaptive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations